(untitled) (International Journal of Communication Systems and Network Technologies, 2025)
Sensor nodes in a network often have low power needs and communicate wirelessly. The challenge of creating a wireless sensor network routing system that uses minimal energy is a significant one. In wireless sensor networks, saving power is crucial to extending the life of the system. Large-scale wireless sensor networks (WSNs) include hundreds or thousands of sensor nodes into a single system. They weigh next to nothing, have a short battery life, and have a low primary storage capacity and computing capability. They can wirelessly monitor environmental or physical parameters. This research presents a performance analysis of many existing routing protocols and a suggested layered distinct tree framework for storing route information in a target tracking application. Multiple sensor nodes are deployed utilizing a comprehensive binary tree data structure to safely store the collected data. Wireless sensor networks can only use so much electricity because of their finite supply of batteries. This resulted in a drastic decrease in the network’s efficiency. Therefore, this study presents a Wireless AdHoc Routing Protocol (WAHRP) for lowering network energy usage. The suggested technique is compared with the current routing protocol called AdHoc On-Demand Distance Vector (AODV) to evaluate the efficiency of the proposed scheme and the resulting part shows the right proof to it in plain manner. This technology is able to identify the precise location of a target, conserve energy, and lengthen the life of a network. The goal is to reduce the amount of power used by the network by putting idle terminals into sleep mode at predetermined times. Several uses place a premium on throughput and care little about latency. Which parameter is preferred ultimately depends on what the application wants. Having a thorough understanding of network architecture and routing protocols that is tailored to the needs at hand is crucial.